The effects of reinforcement with nanoparticles of polyetheretherketone, zirconium oxide and its mixture on flexural strength of PMMA resin - Deepali Barapatre; Surabhi Somkuwar; Sunil Kumar Mishra; Ramesh Chowdhary (European Oral Research)
Purpose: Polymethylmethacrylate denture bases are prone to fracture, so reinforcement of dentures with nanoparticles is required to overcome these challenges. This in-vitro study was done to assess the effect of reinforcement with nanoparticles of polyetheretherketone (PEEK), zirconium oxide (ZrO2) and its mixture on flexural strength of polymethylmeythacrylate resin. Material and methods: A total of 60 acrylic resin specimens measuring 65 mm × 10 mm × 2.5 mm were fabricated. The specimens were divided in to fifteen specimens in each group [control group (C), 3wt% PEEK group (P), 3wt% zirconia group (Z), and hybrid reinforcement of 1.5wt% PEEK and 1.5wt% ZrO2 group (P-Z)]. The flexural strength of the specimens was evaluated using a three-point bending test on a universal testing machine. The statistical analysis was done using one-way analysis of variance (ANOVA), and the intergroup comparison was done using Tukey’s post hoc analysis. Results: The mean flexural strength was maximum in group P-Z (98.73MPa) followed by group P (86.22 MPa) and group Z (84.48 MPa). The mean flexural strength was least in the control group (74.11MPa). One-way ANOVA revealed a highly significant (P<0.01) difference among the groups. Pairwise comparison among groups showed a significant difference (P<0.05) among all the groups except in between groups P and Z where no significant difference was found (P=0.406). Conclusion: Hybrid reinforced PEEK and zirconia could be used as an effective reinforcement material for denture base resin. The hybrid PEEK and zirconia reinforced resin can be an alternative treatment option in patients with heavy occlusal forces and for patients who have previous experience of multiple denture fractures.